Digital Resilience and Financial Stability: Rethinking the Strategic Role of FinTech, AI, and CBDC in Indonesia and Emerging Economies - Prihandini, Wiwiek; Safaria, Siti (Journal of Business, Finance, and Banking, 2025)
In the era of accelerating digital transformation, financial systems in emerging economies face a dual challenge: harnessing the potential of innovation while safeguarding systemic stability. This paper examines the strategic role of Financial Technology (FinTech), Artificial Intelligence (AI), and Central Bank Digital Currency (CBDC) in enhancing financial resilience and ensuring macroprudential stability, with a particular focus on Indonesia as a leading example of digital financial integration in the Global South. Drawing on comparative policy analysis, global regulatory trends, and Indonesia's policy innovations—such as the Quick Response Code Indonesian Standard (QRIS), Bank Indonesia’s Garuda Project, and the Financial Services Authority’s (OJK) regulatory sandbox—this study proposes an integrative framework that links digital innovation with governance architecture and institutional readiness. The findings reveal that while FinTech accelerates inclusion, AI enhances predictive supervision, and CBDCs improve monetary control, their effectiveness depends on adaptive regulation, cross-sectoral coordination, and data governance. The paper also highlights the risks of regulatory fragmentation, algorithmic bias, and digital inequality if innovations outpace institutional preparedness. In response, the study outlines policy recommendations centered on principle-based supervision, digital financial resilience strategies, and ethical frameworks for AI and CBDC. Theoretically, this research contributes to the evolving discourse on digital-era macroprudential governance; practically, it offers a roadmap for policymakers to build robust, inclusive, and sovereign financial ecosystems.